2018
DOI: 10.3390/nu10121926
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages from Mice Administered Rhus verniciflua Stokes Extract Show Selective Anti-Inflammatory Activity

Abstract: The bark of Rhus verniciflua Stokes (RVS) is used as a food additive and herbal medicine for various inflammatory disorders and cancer in Eastern Asia. RVS has been shown to exert anti-inflammatory effects in lipopolysaccharide (LPS)-stimulated macrophages in vitro, but whether oral administration of RVS affects the inflammatory response of macrophage needs to be verified. RVS was given orally to mice for ten days. For isolation of macrophages, intraperitoneal injection of thioglycollate was performed. For det… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Additionally, the concentration of endotoxin in original recombinant ADH (0.87 mg/mL) was 0.09 unit/mL which is equal to 10.8 pg/mL according to calculate conversions [22] , therefore 300 nM ADH contains 0.135 pg/mL LPS. The effective concentrations of LPS to stimulate monocytes/macrophages commonly range from 100 ng/mL to 20 μg/mL [14] , [23] , [24] , [25] , [26] , [27] , [28] . Although the concentration of LPS was extremely low in this study, flow cytometric assay and ELISA were performed on LPS-treated THP-1 cells in order to completely exclude the influences of LPS which is considered an inflammatory activator and able to increase monocytes surface markers expression and pro-inflammatory cytokines production [28] .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the concentration of endotoxin in original recombinant ADH (0.87 mg/mL) was 0.09 unit/mL which is equal to 10.8 pg/mL according to calculate conversions [22] , therefore 300 nM ADH contains 0.135 pg/mL LPS. The effective concentrations of LPS to stimulate monocytes/macrophages commonly range from 100 ng/mL to 20 μg/mL [14] , [23] , [24] , [25] , [26] , [27] , [28] . Although the concentration of LPS was extremely low in this study, flow cytometric assay and ELISA were performed on LPS-treated THP-1 cells in order to completely exclude the influences of LPS which is considered an inflammatory activator and able to increase monocytes surface markers expression and pro-inflammatory cytokines production [28] .…”
Section: Resultsmentioning
confidence: 99%
“…However, a higher level and different pattern of IL-12 production were detected at a lower concentration of FGE in comparison to that in RAW264.7 cells. Kim et al (23) discovered that the activation of NF-κB and IRF-1 proteins by IFN-γ plays a role in the production of IL-12. Furthermore, T-cells, NK cells that release a substantial amount of IFN-γ, are found in insignificant numbers in adherent fractions of peritoneal exudate cells (23).…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear factor κ-B (NF-κB) and interferon regulatory factor-1 (IRF-1) are involved in the production of IL-12, which is then activated by IFN-γ (22). T-cells and NK cells, which release a substantial amount of IFN-γ, are found in insignificant numbers in adherent peritoneal exudate cells (23). As a result, FGE treatment may have induced peritoneal macrophages to create more IL-12 in response to IFN-γ.…”
Section: Immunostimulatory Effects Of Fge On Peritoneal Macrophage Ac...mentioning
confidence: 99%
“…Furthermore, the same study reported that Sumac caused monocyte differentiation through exhibiting selective anti-inflammatory activity without causing overall inhibitory effects on the immune cells. 23 There exist studies indicating that Sumac decreased the CPR levels, which previously increased due to diabetes, cancer, and atherosclerosis. 24 The findings of a study focusing on Sumac indicated that it had the effect of correcting immunosuppression, which occurred due to chemotherapeutics and was particularly effective for regulating WBC deficiency and lymphopenia.…”
Section: Anti-inflammatory Effectmentioning
confidence: 99%